Comparative analysis of methods for isothermal amplification of nucleic acids - O. S. Chemisova; O. A. Tsyrulina; A. L. Trukhachev; A. K. Noskov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2022)
In this review, methods for isothermal amplification of nucleic acids are considered and analyzed, in particular, loop isothermal amplification of DNA and RNA (LAMP/RT-LAMP), helicase-dependent amplification (HDA) and recombinase polymerase amplification (RPA). The advantages and disadvantages of each of the techniques are described. The possibility of their application in the molecular diagnostics of infectious diseases is evaluated. A brief review of the literature on the use of LAMP, HDA, RPA in the diagnostics of viral, bacterial infections and diseases of protozoal etiology was conducted. It has been shown that the LAMP method has a number of advantages over other diagnostic methods: high efficiency, specificity, simplicity, turnaround time and minimum requirements for instrument equipment. As a result, it is concluded that loop isothermal amplification is a promising method for detecting the DNA/RNA of various pathogens. The data on the introduction of the LAMP method in the diagnostics of particularly dangerous bacterial and viral infections, including for the detection of RNA of a new coronavirus infection (SARS-CoV-2) in clinical samples, are presented.